DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI KARET EKS UPP TCSDP DAN SWADAYA DI DESA KOTO DAMAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Dyppo ' Sinaga; Eliza ' '; Suardi ' Tarumun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aimed to analyze the sources and income structure,  distribution and inequality, household income disparity of rubber farmer ex UPP TCSDP and self-help at koto damai village, Kampar kiri tengah district in Kampar region. The method that I use is survey by census sampling technique asmuch as 20 farmers governmental pattern and purposive random sampling technique as musch as 30 farmers ex UPP TCSDP. The analysis technique that is used is the analysis of net income, gini rato, Lorenz curve and t test. The analysis showed that the ex UPP TCSDP rubber farmer’s income from the agricultural sector is rp.42.057.799 per year(88.88%) and from non-agricultural sector is Rp.5.264.000 per year (11.12%). Farmers in the agricultural sector Governmental Pattern Rp. 30,490,039 per year (94.43%) non-agricultural sector is Rp. 1,800,000 per year (5.57%). Farmer’s revenue structure earn their incomes from rubber works eks upp tcsdp Rp.14.047.672 per year (29,69%), and other incomes beside TCSDP rubber, farmers earn their average income around Rp. 33.274.127 per year (70,31%). Rubber farmers earn their average income from their main job around Rp. 12.734.952 per year (39,44%). And for side income, farmers earn around sebesar Rp. 19.555.088 per year(60,56%). The gini ratio index of ex UPP TCSDP rubber farmer’s and self-help farmers in koto damai village is on small inequality of 0.26 and 0.10 on<0.3.The zero hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, meaning that there are differences in household incomes of ex upp tcsdp rubber farmers with the household income of self-help rubber farmer. Keywords : Distribution, Income, Household, Rubber.